The Role of Islamic Religious Education Teachers in Shaping Student Character in the Digital Era of Class VIII at SMP Islam Plus Sabilunnajah - Maulana, M.Fikri; Hernisawati, Hernisawati; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
The rapid development of digital technology influences students' thinking patterns and behavior, so that the role of teachers (PAI) plays a very important role in shaping students' character, especially in terms of morals and morals. They function as educators, mentors, innovators and motivators for students. This research focuses on examining the role of PAI teachers in shaping student behavior in digital developments in class VIII of SMP Islam Plus Sabilunnajah, where there are several declines in student character, especially in the digital era. This research was conducted using a qualitative case study method and data collection was carried out by means of documentation, interviews and observation. The results of the research show that Islamic Religious Education teachers at Islam Plus Sabilunnajah Middle School have an important role in internalizing the principles of Islamic teachings to students through personal example, technology-based learning, as well as strengthening the principles of Islamic teachings in daily activities. Therefore PAI teachers not only have a role as religious teachers, but also as guides in shaping students' behavior amidst digital developments